DENTAL ASSISTANCE TO MILITARY PERSONNEL OF THE ARMED FORCES OF UKRAINE - Lavrin, O. Ya.; Avdeev, O. V.; Romanjuk, N. Ye.; Bedenyuk, O. A. (International Journal of Medicine and Medical Research, 2022)
Background. At present, the formation of military units of the Armed Forces of Ukraine during mobilization takes place with underlying high dental morbidity of the population of the country. Objective. The aim of this research was to study dental health of the personnel of military units and the problem of providing dental care to military personnel according to the analysis of modern scientific literature. Methods. The following research methods were used to analyse dental care for military personnel, namely: bibliographic, analytical, systems approach. Results. Hygiene of the oral cavity is mandatory in military units and should be routinely carried out. It was found that the main reason for seeking dental care among military personnel was treatment of major dental diseases. A low number of military personnel seeking for dental preventive examination was noted that proved a low level of primary prevention among this category of people. Conclusions. Therefore, the obtained data on the state of dental health of military personnel require a purposeful approach to organization of prophylaxis and prevention of complications through professional hygiene and early prosthetics.